Nanocapsules with excellent biocompatibility and stability in protein solutions - Arjaree Jobdeedamrong (2022)
Silica nanocapsules (SiO2NCs) are usually prepared with cationic surfactants that are not cytocompatible. Dialysis can be used to remove surfactants but leads to instability of the SiO2NCs when they are in the presence of proteins or biological media. Herein, SiO2NCs stabilized with a reactive surfactant are synthesized to prevent leaching upon dialysis. The SiO2NCs show superior stability and biocompatibility compared with SiO2NCs prepared with conventional surfactants. The SiO2NCs can be used in self-healing materials, smart agriculture and biomedical applications.